Análise temporal e espacial da mortalidade por câncer em Sergipe (1980-2018) - Lima, Marcela Sampaio (2021)
Cancer is one of the main health problems worldwide and has a considerable impact on population morbidity and mortality and health systems, especially in countries that are in epidemiological transition. Its nature is complex and multicausal. The objectives of this study were to describe the mortality trend for all cancers combined and for the main topographies in the state of Sergipe and in the health regions, separately, from 1980 to 2018; and to analyze their spatial distribution. As a methodology, an exploratory and analytical ecological study of time series with spatial analysis was carried out, using consolidated data from the Aracaju Population-Based Cancer Registry and the Mortality Information System for the state of Sergipe for temporal analysis and from the Online Mortality Atlas for spatial analysis. Crude and age-standardized mortality rates were calculated based on census populations and inter-census estimates provided to DATASUS by the Brazilian Institute of Geography and Statistics (IBGE). Time trends were calculated using the Joinpoint Regression Program of the National Cancer Institute, USA. Spatial statistics were performed using TerraView 4.2.2 software, adopting the local empirical Bayes model for rate smoothing and the Global Moran Index for the evaluation of spatial autocorrelation for adjusted and bayesian rates. Thematic maps were constructed using the QGIS 3.10 software. The cartographic base of Sergipe and the geocodes of the municipalities were obtained from IBGE. In this period, there were 34,214 cancer deaths in Sergipe, excluding non-melanoma skin cancers. The age-standardized mortality rate (ASR) for all cancers combined was 70.1 and 57.9 per 100,000 men and women, respectively. There were upward trends until 2005 in males and from 1987 to 2006 in females, becoming steady since then. In the last five years, the mortality ASRs were 97.2 and 72.0 for males and females, respectively. The main topographies were: prostate (21.3), trachea/bronchus/lung (11.7), stomach (6.5), oral cavity (5.4) and liver/intrahepatic bile ducts (5.1) in males; and breast (13.8), trachea/bronchus/lung (6.6), cervix (6.4), colon/rectum (5.8) and central nervous system (3.6) in females. The most populous municipalities showed the highest absolute number of deaths from cancer. There was no spatial autocorrelation for the mortality ASRs, only for rates smoothed by the Bayesian model for all cancers combined and for the main topographies analyzed, in both sexes. Some patterns of priority municipalities were observed: a cluster forming a strip in the east/coastal region of the state for breast cancer; a cluster in the west/south region for prostate cancer; and a cluster from the central region to the east/south for colon/rectum cancer in females, among others. The results showed that although there was an increase in mortality rates due to cancers associated with Western lifestyle and aging, such as prostate, breast and colon/rectum, high rates of cancers associated with poverty and infections, such as stomach, cervix, and oral cavity, still persist in Sergipe. This profile is also observed in countries facing epidemiological transition. The patterns of spatial distribution observed indicated the municipalities (and regions) of higher priority, which had high mortality rates and neighbors also with high rates, as well as those of intermediate priority, in the management of cancer in the state.